2003
DOI: 10.1038/sj.bjp.0705569
|View full text |Cite
|
Sign up to set email alerts
|

Allergen‐induced inflammation and airway epithelial and smooth muscle cell proliferation: role of Jun N‐terminal kinase

Abstract: 1 Chronic cellular inflammation and airway wall remodelling with subepithelial fibrosis and airway smooth muscle (ASM) cell hyperplasia are features of chronic asthma. Jun N-terminal kinase (JNK) may be implicated in these processes by regulating the transcriptional activity of activator protein (AP)-1. 2 We examined the effects of an inhibitor of JNK, SP600125 (anthra [1,9-cd] pyrazole-6 (2 H)-one), in a model of chronic allergic inflammation in the rat. 3 Rats sensitised to ovalbumin (OA) were exposed to OA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 38 publications
3
42
0
Order By: Relevance
“…SP600125 activity has been reported in a number of rodent models of pulmonary disease, including single and chronic allergen challenge in the rat [45,46] and mouse [47], and bleomycin-induced injury and repair in the mouse [48]. Some of these studies have been repeated and confirmed using proprietary JNK inhibitors from a distinct chemical class, a JNK inhibitor from a discovery programme at Serono [49,50] and AP-1 activation inhibitors [51].…”
Section: Inhibition Of C-jun N-terminal Kinasementioning
confidence: 85%
See 1 more Smart Citation
“…SP600125 activity has been reported in a number of rodent models of pulmonary disease, including single and chronic allergen challenge in the rat [45,46] and mouse [47], and bleomycin-induced injury and repair in the mouse [48]. Some of these studies have been repeated and confirmed using proprietary JNK inhibitors from a distinct chemical class, a JNK inhibitor from a discovery programme at Serono [49,50] and AP-1 activation inhibitors [51].…”
Section: Inhibition Of C-jun N-terminal Kinasementioning
confidence: 85%
“…A novel observation in chronically allergen-challenged rats and mice was that JNK inhibitor caused significant inhibition of both airway smooth muscle proliferation and goblet cell hyperplasia, which are common features of the asthmatic airway [46,47]. It remains unclear whether this effect of JNK inhibitor was due to inhibition of growth factor expression or via direct inhibition of cell cycle mechanisms.…”
Section: Proliferationmentioning
confidence: 99%
“…[30][31][32] Interestingly, the numbers of eosinophils in the bronchial tissue were not reduced after pre-treatment with SP600125. [32] Our present result that inhibition of JNK activity does not increase but rather decreases apoptosis of eosinophils is in line with the inability of SP600125 to reduce tissue eosinophilia.…”
Section: Discussionmentioning
confidence: 98%
“…[32] Our present result that inhibition of JNK activity does not increase but rather decreases apoptosis of eosinophils is in line with the inability of SP600125 to reduce tissue eosinophilia. However, SP600125 reduces the production of several cytokines and chemokines [30][31][32] as well as inhibits several other kinases [28] and thus the net effect of SP600125 on pulmonary inflammatory indices is a result of a combination of all its effects.…”
Section: Discussionmentioning
confidence: 99%
“…MAP kinases modulate gene transcription, mainly through activation of transcription factors. In particular, the MAP kinase c-Jun NH 2 -terminal kinase (JNK) and its downstream transcription factor c-Jun have been associated with inflammation, for example, in colitis (Assi et al, 2006), asthma (Eynott et al, 2003), and arthritis (Han et al, 2001). Moreover, glomerular JNK activation has been demonstrated in experimental glomerulonephritis (Seto et al, 1998).…”
mentioning
confidence: 99%